The case-orientedness of qualitative comparative analysis (QCA) - Rihoux, Benoît (Teorija in praksa, 2015)
This article addresses the development of Qualitative Comparative Analysis (QCA) from its launching in 1987 until present. We surveyed from the perspective of QCA's proclaimed "case-orientedness". We started by examining the foundations of QCA and the way those foundations have evolved over three decennia, in particular in terms of the connection with case-oriented work. Furthermore, we demonstrate that this was and is still an important facet of QCA both as an approach and as a set of techniques. Additionally, in more concrete terms, we go through all the practical QCA operations and demonstrate that virtually in every step of the QCA procedure; there is a potential dialogue with the individual cases, whether they are defined at the macro-, meso- or micro levels. Finally, we analyze the current state of affairs which seems to run against the articulation between "deep" (in particular ethnographic) case-oriented work and QCA, and propose avenues to engage more thoroughly in deeper case-informed QCA work.
Keywords: Comparative analysis; Kvalitativna analiza; Primerjalna analiza; primerjalne metode; Qualitative analysis